PERSEPSI SISWA TERHADAP PELAKSANAAN UPACARA BENDERA DALAM PEMBENTUKAN SIKAP NASIONALISME - Mey Rizka Zayulate; Hermi Yanzi; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2015)
The objectives of this research were to describe and explain the perception of students on the implementation of a flag ceremony in forming of the attitude of nationalism. The method used in this study was descriptive quantitative research. The population in this research were 125 people and 31 people as the sample. Data collecting technique was using interview and analyzing the data was using percentage. The results of the study showed that the indicator of understanding as many as 6,45 percent students in negative criteria or do not understand, 58,06 percent students in tended to be positive criteria. In indicator of responses as many as 22,58 percent were disagree with the flag ceremony, 45,16 percent were agree with the flag ceremony. In indicator of hope as many as 22,58 percent were disagree with the flag ceremony formed the nationalism, 41,93 percent were agree with the flag ceremony formed the nationalism.Tujuan penelitian ini untuk mendeskripsikan dan menjelaskan tentang Persepsi Siswa Terhadap Pelaksanaan Upacara Bendera Dalam Pembentukan Sikap Nasionalisme Siswa, penelitian ini menggunakan metode deskriptif kuantitatif. Populasi dalam penelitian ini 125 orang dengan sampel 31 orang. Pengumpulan data menggunakan teknik angket dan analisis data menggunakan teknik persentase. Hasil penelitian menunjukan bahwa pada indikator pemahaman sebanyak 6,45% siswa masuk dalam kriteria negatif atau tidak paham, 58,06% siswa masuk dalam kriteria cenderung positif. Pada indikator tanggapan sebanyak 22,58% tidak setuju dengan pelaksanaan upacara bendera, 45,16% setuju pelaksanaan upacara bendera. Pada indikator harapan sebanyak 22,58% tidak setuju pelaksanaan upacara bendera membentuk sikap nasionalisme, 41,93% setuju pelaksanaan upacara bendera membentuk sikap nasionalisme.Kata kunci : nasionalisme, persepsi siswa, upacara bendera